Compensation And Employee Loyalty Among Health Workers In Nigeria - Akhigbe, Omoankhanlen Joseph; Ifeyinwa, Emmanuel Ethel (Archives of Business Research, 2017)
Compensation and employee loyalty has been an issue of great concern in organizations over the years. This problem prevails in the contemporary society especially in Nigeria. It therefore becomes imperative to investigate and determine the influence of compensation on employee loyalty. The research was a survey of eight private hospitals that were purposively selected in Port Harcourt. To carry out this research, relevant literature was reviewed to confirm the existence of the problem. The components of the independent and dependent variables were examined. Questionnaire was the major instrument that was used to collect data for the study. The study sample size was determined using Taro Yamen’s formula and Spearman Rank Order correlation coefficient was used to analyse the data. It was found that there is significant positive relationship between compensation and employee loyalty. It was recommended among others that regular payment of employees salary will impact positively on the cognitive loyalty of the employees. Increment of employee salary enhances positive reactions of the employees thereby inducing loyalty. Organizations should encourage the employees to own shares as it induces cognitive loyaltyamong workers. Equity based compensation influences employee behaviour positively thereby encouraging retention of employees. Organisations should consider occupational hazards of hospital environment when fixing the pay of the employees.